Structural and Phase Transformations in Ti-B[4]C System Formed when Melting the Composition Film/Substrate by an Intense Electron Beam - Ivanov Yu. F. Yuriy Fedorovich; Khasanov O. L. Oleg Leonidovich; Bikbaeva Z. G. Zulfa Gadilzanovna; Petyukevich M. S. Mariya Stanislavovna; Teresov A. D.; Shugurov V. V. Vladimir Viktorovich; Ivanova О. V. Оlgа; Klopotov A. A. Anatolii (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen